IoT-based Framework for Coordinating Smart Home - Azlina, Binti Ahmadi Julaihi; Nur Hazierah, Binti Mazlan; Abdul Rahman, Mat (UNIMAS Publisher, 2021)
IOT RFID Door Open Notification for Homestay is a system that focuses on the use of RFID as a door lock and keeps track the database of Homestay’s guest check-in and check-out time data. By implementing this project, the homestay owner can view and update the check-in and check-out time of their guest whenever required. MySQL will be used in this project for database support and logging the Homestay Web-based System. In this paper, a new framework with Radio Frequency Identification technology (RFID) applied to homestay door lock is exposed. In order to validate the designed framework, an experiment to configure the speed capture by the RFID reader was carried out